Reasons for Zahedan’s women for not referring to delivery ward for child delivery - M Salehi; Z Ghasemi Pour (JRI, 2002)
Maternal and infantile mortality are important health indicators of every society due to pregnancy incidents. Maternal and infant mortality and also neonatal tetanus incidents have direct relation with delivery condition. Neonatal tetanus and mortality among mothers and newborns have direct relation with delivery in non-hygienic condition. Non-hygienic delivery rate is very high in Sistan and Baluchestan province. Even in the city of Zahedan with a population of 450000, where as access to maternity hospital is possible for all residents of this city, 50-60 % deliveries take place at home. In this study, the reasons of women were investigated for not referring to maternity hospital for delivery. The method of research was case control. Case group was selected from those women whose last deliveries had not taken place in maternity hospital and referred to health centers to vaccinate their children (no. 482). Control group was selected randomly among women who referred to hospital to give birth (no. 198). Hospital’s high fee (38%), easy delivery at home (19%), fear from cesarean and drugs adverse reaction (13%) were the most prevalent reason for not giving birth at hospital. Employment and literacy rates of those women who had given birth at home were lower than control group. They were mainly from Suni and Baluch ethnic. In order to minimize the cultural barriers of referring to maternal hospital, we advise the respectful officers, to make insurance public, lower the treatments fee, held training programs and provide hygienic conditions with low cost for out of hospital deliveries.
Keywords: Home delivery, Maternal hospital, Iran